The Role of Postcolonial Social Background and Gender in Shaping the Characters of Dewi Ayu and Johan in Beauty Is a Wound - Elvira, Dwi; Azzahra, Lisa; Haliq, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines how postcolonial social background comprising economic inequality, patriarchal norms, and colonial legacy influences the character development of Dewi Ayu and Johan in Eka Kurniawan’s novel Cantik Itu Luka. Utilizing a descriptive qualitative design with close reading of the 2018 Gramedia edition, twelve passages illustrating economic, patriarchal, and historical dimensions were selected as primary data. These excerpts underwent manual open coding and thematic interpretation of characters’ attitudes, actions, and identities. Results indicate that economic inequality prompts commodification of bodies and personal narratives; patriarchal norms provoke both symbolic and practical resistance through narrative techniques, silent defiance, and shifting notions of beauty; and colonial legacy informs Johan’s identity reconstruction via re-membering practices and linguistic decolonization. The interrelation of these dimensions reveals the complexity of oppressive social structures that simultaneously foster spaces for resistance, thereby contributing to postcolonial literary scholarship and gender discourse in Indonesia.